Daya Terima dan Nilai Gizi Snack Bar Modifikasi Sayur dan Buah Untuk Remaja Putri - Dwi Yulia Estika Sari; Dudung Angkasa; Prita Dhyani Swamilaksita (Jurnal Gizi, 2017)
High fat and low dietary fiber food among teenagers might be responsible for future adverse health effect. Snack bar which contained fruit and vegetable can be a favorable food for teenagers since it can increase fruit and vegetable consumption, ready-to-eat and relatively affordable.  This study examine the acceptability characteristic of a snack bar which was modified with soybean flour, fruits and vegetables complementation. This experimental study provided 3 (thee) formulas namely F1 (40:60), F2 (50:50),  F3(60:40) based on ratio of soybean flour to Salacca zalacca. All formulas were laboratory analyzed forproximate, crude fiber, and iron content. Acceptability level were assessed by 25 semitrained panelists. Total 25 Panelists were used to assess the acceptability of formulasusing a Visual Analogue Scale. Oneway Anova was used for assessing the effect of soybean flour and Salacca zalacca complementation to panelist acceptability.  Result showed that the soyflour and Salacca zalacca modification significantly affect the taste, aroma and texture of the snack bar (p <0.05) but no effect on the color (p> 0.05). The most favorite formula was F2 (50% soybean flour: 50% fruits). Energy, protein, fat, crude fiber and Fe content tend to increase from F1 to F3. Complementation of soyflour and fruits in balance ratio may produced the optimalacceptability and increased the nutrient content of snack bar.Keywords: snack bar, fruit and vegetable, soyflour, teenagers,  Salacca zalacca